REVIEW OF THE PROGRAMME: SR. MARIA OPIELA, SR. MAŁGORZATA KAPUT, SR. EDYTA PIEKARZ, SR. AGNIESZKA KORNOBIS, SR. ZOFIA ZYMRÓZ, SR. STANISŁAWA CHUDZIK, PRESCHOOL EDUCATION PROGRAMME BASED ON THE PEDAGOGICAL CONCEPTION BY BL. EDMUND BOJANOWSKI, Published by WERSET, LUBLIN 2020, PP. 117. - Anna Klim-Klimaszewska (Rozprawy Społeczne)
Abstract The review is about the preschool education program by Edmund Bojanowski, who devoted himself to post-epidemic orphans, establishing for them a shelter, the so-called "Institute" or "House of Mercy". He also took care of other rural children, organizing nurseries for them. He based his upbringing on the rich traditions of the Polish countryside, its spiritual wealth, relationships with the earth and agricultural activities. As a reliable means of education considered the nature, religion and history, which were to intertwine into a harmonious synthesis of work, love for God and neighbor, and practical love for the polish land and culture.